2019
DOI: 10.3758/s13414-019-01679-7
|View full text |Cite
|
Sign up to set email alerts
|

Visual salience, not the graspable part of a pictured eating utensil, grabs attention

Abstract: Three experiments used compatible and incompatible mappings of images of eating utensils to test the hypothesis that these images activate affordances for grasping with the corresponding hand when the required response is a key-press. In Experiment 1, stimuli were photographs of a plastic spoon oriented on the horizontal axis, with the handle location varying randomly between left and right. Participants were instructed to respond to the handle or the tip, with a compatible mapping in one trial block and an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 29 publications
(54 reference statements)
10
23
0
Order By: Relevance
“…The larger compatibility effect with tip-relevant than with handle-relevant in our prior study (Xiong et al, 2019) is in agreement with this analysis, and we expected to replicate that result for 2D images. If the salient tip is the primary factor with 3D objects, they also should show the same result pattern to a similar extent.…”
Section: Methodssupporting
confidence: 87%
See 3 more Smart Citations
“…The larger compatibility effect with tip-relevant than with handle-relevant in our prior study (Xiong et al, 2019) is in agreement with this analysis, and we expected to replicate that result for 2D images. If the salient tip is the primary factor with 3D objects, they also should show the same result pattern to a similar extent.…”
Section: Methodssupporting
confidence: 87%
“…In a prior study, we followed up on the idea that the spoon’s handle produces a grasping affordance using only 2D images, which allows for tighter stimulus control and more trials to be conducted in a given period of time (Xiong et al, 2019). Experiment 1 used simple displays with photographs of a single, centred spoon, for which the side to which the tip was located (as well as the handle) varied randomly from trial to trial.…”
Section: Variants Of Object-based Correspondence Used As Evidence Formentioning
confidence: 99%
See 2 more Smart Citations
“…But, this cannot be definitively concluded without ruling out variants of customary accounts of S-R compatibility effects. In fact, numerous studies have found that findings initially attributed to grasping affordances on closer empirical inspection often are a result of spatial factors such as the location of a visually salient object property (e.g., Song, Chen, & Proctor, 2014; Xiong, Proctor, & Zelaznik, 2019). Thus, object-based compatibility effects have been obtained for situations in which they would not be expected to occur from the affordance view, such as with both broken handles (e.g., Ambrosecchia, Marino, Gawryszewski, & Riggio, 2015), disembodied objects (e.g., Cho & Proctor, 2010), and even when feet are used as effectors (e.g., Phillips & Ward, 2002; Symes, Ellis, & Tucker, 2005).…”
Section: Activation Regardless Of Context: Tucker and Ellismentioning
confidence: 99%